2016
DOI: 10.1161/strokeaha.116.012639
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Guidelines on Clinical Practice

Abstract: Background and Purpose-Since its introduction, controversy has existed about the administration of intravenous heparin for the treatment of acute ischemic stroke. We studied trends in the intravenous heparin use during a 6-year time period and the potential influence of clinical guidelines in national language on intravenous heparin administration in Korea. Methods-On the basis of a prospective nationwide multicenter stroke registry, we collected data on patients with acute ischemic stroke who arrived within 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…It could also increase complications like symptomatic hemorrhagic transformation or heparin-induced thrombocytopenia. Therefore, the use of intravenous unfractionated heparin has recently been decreased [ 65 ]. Given the high risk of bleeding complication, the use of intravenous heparin is not recommended for perioperative stroke.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…It could also increase complications like symptomatic hemorrhagic transformation or heparin-induced thrombocytopenia. Therefore, the use of intravenous unfractionated heparin has recently been decreased [ 65 ]. Given the high risk of bleeding complication, the use of intravenous heparin is not recommended for perioperative stroke.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Using registry data, it was shown that the use of intravenous heparin for the treatment of AIS decreased between 2008 and 2013 in South Korea, and this decrease might be attributable to the successful implementation of the stroke guidelines developed by the CRCS. 17…”
Section: Crcs-k As a Research Networkmentioning
confidence: 99%
“…There was no immediate, stepwise effect of new cientific information and national guidelines on clinical practice concerning heparin as treatment for progressive ischemic stroke (Eriksson et al 2010). The use of intravenous heparin for acute ischemic stroke treatment has decreased in Korea, and this change may be attributable to the spread and successful implementation of regional clinical practice guidelines (Chung et al 2016).…”
Section: The Use Of Heparin In Clinical Practicesmentioning
confidence: 99%